Media coverage and food commodities: Agricultural futures prices and volatility effects - Miguel Almanzar; Maximo Torero (University of Bonn, Center for Development Research (ZEF), 2017)
We examine how media coverage of fluctuations in the price of agricultural commodities affects these prices and their volatility. We develop a unified empirical framework to analyze the media's effects on both returns and volatility using insights from the literature. We use daily prices of futures contracts for soybeans, hard wheat, soft wheat, rice, and maize, complemented by a unique dataset that follows a comprehensive set of global media outlets and uses an algorithm to determine sophisticated relationships among phrases in a news article which signal an increase or decrease in the price of those four commodities. We find price effects that are economically important in size. Our estimates imply a net increasing effect of media coverage on the price of these four commodities; these effects are mostly concentrated in 2012 and from 2015 onwards, meaning that these effects are important in periods of both high and low prices. Across commodities, the price effects are concentrated in soybeans and maize. We find robust evidence that media coverage decreases volatility for these agricultural commodities on average for the period we study. The effects on volatility balance each other, with decreasing price coverage decreasing the variance of returns and increasing price coverage increasing the variance of returns of futures contracts of these commodities; however, the increase is than the decrease. Our results suggest that media coverage increases periods of normal volatility and decreases periods of excessive volatility. These results point to the potential of using media coverage to bring attention to price surges and to decrease volatility during food crises or times when there is above-normal volatility. The dynamics between the price of agricultural commodities and media coverage may help prevent knee-jerk policy reactions by discouraging market overreaction, encouraging market stability, and promoting food security. They highlight crucial role of providing appropriate information as fast as possible so media coverage and reflects the fundamentals that drive food commodity prices.
Keywords: G13; G14; Q11; Q14; Q18; 330; sentiment analysis; textual analysis; agricultural food commodities; price spikes; volatility; media coverage; market efficiency